Reliable reference genes for gene expression analyses under the hypomagnetic field in a migratory insect - Zhang, Ying; Zeng, Luying; Wei, Yongji; Zhang, Ming; Pan, Weidong; Sword, Gregory A.; Yang, Fei; Chen, Fajun; Wan, Guijun (Frontiers in Physiology, 2022)
Manipulating the hypomagnetic field (HMF), which is the absence or significant weakening (<5 μT) of the geomagnetic field (GMF), offers a unique tool to investigate magnetic field effects on organismal physiology, development, behavior and life history. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) has been utilized to study changes in gene expression associated with exposure to the HMF. However, selecting appropriate reference genes (RGs) with confirmed stable expression across environments for RT-qPCR is often underappreciated. Using three algorithms (BestKeeper, NormFinder, and GeNorm), we investigated the expression stability of eight candidate RGs when exposed to the HMF condition versus local GMF during developmental from juveniles to adults in the migratory insect pest, the brown planthopper Nilaparvata lugens. During the nymphal stage, RPL5 & α-TUB1, EF1-α & ARF1, RPL5 & AK, EF1-α & RPL5, and ARF1 & AK were suggested as the most stable RG sets in the 1st to 5th instars, respectively. For 1- to 3-day-old adults, AK & ARF1, AK & α-TUB1, AK & ARF1 and EF1-α & RPL5, AK & α-TUB1, AK & EF1-α were the optimal RG sets for macropterous and brachypterous females, respectively. ACT1 & RPL5, RPL5 & EF1-α, α-TUB1 & ACT1 and EF1-α & RPL5, ARF1 & ACT1, ACT1 & ARF1 were the optimal RG sets for macropterous and brachypterous males, respectively. These results will facilitate accurate gene expression analyses under the HMF in N. lugens. The verification approach illustrated in this study highlights the importance of identifying reliable RGs for future empirical studies of magnetobiology (including magnetoreception) that involve magnetic field intensity as a factor.